(untitled) (Nordic Journal of African Studies, 2002)
The focus of this article is on new marital forms of women in a growing provincial town of Masvingo in Southern Zimbabwe. The study shows that many urbanites were turning to alternative marital forms, especially to what is commonly referred to in Zimbabwe as mapoto, a loosely structured relation with a man which allows the woman to retain control of her life in terms of decision making. The fluidity of the urban situation made mapoto a viable option. Though one of the advantages of mapoto unions is their ability to operate outside the strictures imposed by tradition or the law, some form of legal recognition of mapoto might be useful in cases where one of the cohabiting partners is seeking legal redress after the break-up of a union. (Ed.)